Shiga toxin-producing Escherichia coli (STEC) other than the top-7: multiplex PCR assays development and validation for detection and identification of the predominant serogroups in cattle feces. - Ludwig, Justin (Kansas State University, 2019)
Shiga toxin-producing E. coli (STEC) are major food borne pathogens that cause mild to severe hemorrhagic colitis in humans. Seven serogroups, which include O26, O45, O103, O111, O121, O145 and O157, considered the ‘top-7 STEC’, cause a majority of food borne STEC infections. Cattle are a major reservoir for the STEC. These organisms reside in the hindgut and are shed in the feces. Additionally, cattle harbor a number of other serogroups (n=113) of STEC. A few of the serogroups have been implicated to cause sporadic human infections. Traditionally, serogrouping of E. coli is done by agglutination reaction with serogroup-specific antisera. Multiplex PCR (mPCR) assays targeting STEC serogroups, other than the top-7, were designed, optimized, and validated. The assays targeted one or more serogroup-specific genes, wzx, wzy, gnd, wbdA of the O-antigen gene cluster. A total of 11 sets of mPCR assays targeting 113 serogroups of STEC were designed and validated with known strains of STEC. The assays were utilized to identify serogroups of E. coli strains (n=358), positive for stx1, stx2 (Shiga toxins 1 and 2), and or eae (intimin) genes, and negative for the top 7 serogroups, isolated from fecal samples collected from commercial; feedlots. Of the 358 strains from multiple feedlots located in two states, 298 (83.2%) strains belonged to 21 serogroups and 60 strains (16.8%) were unidentifiable. The twenty one sergogroups included O168 (29.9%), O109 (17.9%), O131 (8.1%), O2 (7.0%), O104 (4.7%), O171 (4.2%), O74 (3.6%), O8 (2.8%), O136 (0.84%), O178 (0.56%), O102 (0.56%), O175 (0.56%), O98 (0.28%), O118 (0.28%), O113 (0.28%), O96 (0.28%), O76 (0.28%),O35 (0.28%), O20 (0.28%), O160 (0.28%), and O169 (0.28%). The detection of the STEC strains indicated that serogroups, O2, O74, O109, O131, O168, and O171, were the most predominant. A six-plex PCR was designed and validated to detect the prevalence of the top six major non top-7 STEC in cattle feces from feedlot cattle. Among the six serogroups of the major non-top 7 STEC, serogroups of O2 (48.7%), O109 (88.1%), O168 (67.9%), and O171 (80.4%) were the dominant serogroups in cattle feces collected from commercial feedlots. Fecal samples that contained the six serogroups were also positive for the three major virulence genes, stx1, stx2, and eae. In conclusion, cattle harbor and shed in the feces a number of serogroups of STEC other than the top 7, with O2, O109, O168, and O171 being the predominant STEC. The potential risk of these STEC to cause human infections is not known.
Keywords: Shiga toxin; E.coli; Not top 7